2008
DOI: 10.1111/j.1745-9125.2008.00110.x
|View full text |Cite
|
Sign up to set email alerts
|

Romantic Partners' Influence on Men's Likelihood of Arrest in Early Adulthood*

Abstract: Female romantic partners' influence on official crime occurrence for men across a 12-year period in early adulthood was examined within a comprehensive dynamic prediction model including both social learning and social control predictors. We hypothesized that relationship stability, rather than attachment to partner, would be associated with reduced likelihood of crime, whereas women's antisocial behavior would be a risk factor, along with deviant peer association. Models were tested on a sample of at-risk men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 46 publications
5
79
0
Order By: Relevance
“…In addition to the characteristics of the romantic relationship, scholars have contended that the personal characteristics of the romantic partner also likely influence the probability of desistance (Capaldi et al, 2008; Giordano et al, 2007; Simons et al, 2002). The argument is that conventional partners are apt to promote socially acceptable activities, whereas antisocial partners are likely to advance situations and opportunities involving deviant behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the characteristics of the romantic relationship, scholars have contended that the personal characteristics of the romantic partner also likely influence the probability of desistance (Capaldi et al, 2008; Giordano et al, 2007; Simons et al, 2002). The argument is that conventional partners are apt to promote socially acceptable activities, whereas antisocial partners are likely to advance situations and opportunities involving deviant behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Simons, Stewart, Gordon, Conger, and Elder (2002) found that quality of romantic relationship was associated with a reduction in crime for both males and females. Similarly, Capaldi, Kim, and Own (2008) found that stability of relationship (an indirect measure of relationship quality) predicted a decreased likelihood of arrest in their sample of young adult males. Finally, Giordano, Lonardo, Manning, and Longmore (2010) examined the extent to which various dimensions of adolescent romantic relationships are associated with delinquency.…”
Section: The Effect Of Being In a Relationship Versus Relationship Qumentioning
confidence: 90%
“…As a child grows older, socializing influences of the family give way to peers and adults outside the home. While there is individual variability in how this dynamic unfolds during adulthood, it is expected that spouses and intimate partners are particularly influential at this time (Capaldi, Kim, & Owen, 2008; Jaffee, Lombardi, & Coley, 2013; Rhule-Louie & McMahon, 2007; Sampson & Laub, 1990, 1993; Sampson, Laub, & Wimer, 2006; Simons et al, 2002). This basic proposition—that antisocial partners and the quality of romantic relationships influence crime to a greater extent in adulthood than do others—has been empirically supported in several studies: their own (Sampson & Laub, 1990, 1993; Sampson et al, 2006) and those of others (Capaldi et al, 2008; Jaffee et al, 2013; Rhule-Louie & McMahon, 2007; Simons et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Romantic relationships, for example, were theorized by Sampson and Laub (1990) to act as a turning point, and subsequent research indicated that the protective effects of marriage (Sampson & Laub, 2005) and, in particular, positive romantic relationships (Capaldi, Kim, & Owen, 2008) are quite strong for men. Specifically, Capaldi et al (2008) found that the desistance effects of romantic relationships for men depend on both relationship stability and the antisocial behavior of romantic partners.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Romantic relationships, for example, were theorized by Sampson and Laub (1990) to act as a turning point, and subsequent research indicated that the protective effects of marriage (Sampson & Laub, 2005) and, in particular, positive romantic relationships (Capaldi, Kim, & Owen, 2008) are quite strong for men. Specifically, Capaldi et al (2008) found that the desistance effects of romantic relationships for men depend on both relationship stability and the antisocial behavior of romantic partners. However, given the particular likelihood of domestic violence in women's romantic relationships (Brown, Miller, & Maguin, 1999), one might expect that this protective effect may not be nearly as strong for women as it is for men (Leverentz, 2006).…”
Section: Literature Reviewmentioning
confidence: 98%